The 'pay to be paid' rule shipowner's bankruptcy and direct actions against P & I clubs - Finnern, Christian (Centre for Law and Society, 2026)
The insurance cover rendered by Protection & Indemnity Clubs ("P&I Clubs") is as essential for shipowners' business in the 21st century as it was for shipowners when the first of those insurance associations, the Shipowners' Mutual Protection Society, was established by Peter Tindall in 1855. 1 Thereby, he reacted upon the necessity to protect the shipowners of those days against the possibility of unlimited liability. Such a risk was probably due to a considerable potential increase of liability caused by the technological developments of the 19th century, in particular the newly developed possibilities of steam ships. Before this association was established, shipowners were not able to obtain insurance cover for the whole value of their vessel, because hull insurers accomplish no more than a 'limited public liability protection' covering only three-quarters of a claim; a shipowner therefore had to cover the last quarter by himself.2 The last quarter was in turn covered by virtue of his membership in one of the newly established associations.